Synthesis of solketal over zirconia based acid catalysts - Reena, SS; Shamshuddin, SMZ; Vasantha, VT; D’Souza, JQ (Bangladesh Journal of Scientific and Industrial Research, 2019)
Microwave assisted synthesis of ‘solketal’ over zirconia (ZrO2) and its modified forms (Mo(VI)/ZrO2, W(VI)/ZrO2 and V(V)/ZrO2) coated on honeycomb monoliths is reported. The solid acids were coated on honeycomb monoliths by ‘dip and dry’ method and characterized for their surface acidity, crystalinity, functionality, morphology and elemental analysis by using techniques such as NH3-Temperature programmed desorption (NH3-TPD), powder X-ray diffraction (PXRD), Fourier transform-infrared spectroscopy (FTIR), Scanning electron microscopy (SEM) and Inductively coupled plasma-optical emission spectroscopy (ICP-OES). The honeycomb monoliths coated with solid acids were employed as catalysts in the condensation of glycerol with acetone to synthesize solketal under microwave irradiation conditions. The reaction conditions such as molar ratio of the reactants (glycerol: acetone), reaction temperature, reaction time were studied to obtain highest possible yield of solketal with greater selectivity. The catalytic activity of honeycomb catalytic material was compared with the powder forms of the catalysts. 98% yield of solketal with 98% selectivity was achieved over Mo(VI)/ZrO2 coated on a honeycomb monolith in a very shorter reaction time of 8 min at 60 oC under microwave heating. These honeycomb catalytic material were found to be easily reactivable and reusable atleast for 6 reaction cycles. Hence, honeycomb catalysts were found to be efficient, economical and effective in the synthesis of value added chemical such as solketal. A possible mechanism for the formation of solketal is proposed. Bangladesh J. Sci. Ind. Res.54(1), 31-38, 2019